PEMENUHAN HAK POLITIK PENYANDANG DISABILITAS SEBAGAI PARTISIPAN PILKADA DI KOTA SEMARANG - Cielo Kenya Cyrilla; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2026)
Fulfillment of political rights is an essential part of the principle of democracy that guarantees equality for all citizens, including persons with disabilities. In practice, persons with disabilities still face various obstacles in participating in the political process, particularly in regional head elections. These obstacles include limited accessibility to polling stations, a lack of inclusive election outreach, and problems in registering voters with disabilities. This study aims to analyze the implementation of election outreach and education for persons with disabilities as participants in the regional elections in Semarang City and to assess the availability of accessibility for persons with disabilities in the election process. This study uses a qualitative research method with a descriptive approach. Data collection was conducted through observation, interviews, and documentation techniques with informants consisting of stakeholders at the Semarang City General Elections Commission (KPU), the disability community, and persons with disabilities as election participants. The results show that election organizers have made various efforts to fulfill the political rights of persons with disabilities through election outreach and education in collaboration with the disability community and the provision of several accessibility facilities at polling stations. However, several obstacles remain in its implementation, such as inaccurate data collection for voters with disabilities, limited physical accessibility at polling stations (TPS), and a lack of supporting facilities appropriate to the needs of various types of disabilities. These conditions have the potential to impact the level of political participation of people with disabilities in regional elections. Therefore, improvements are needed in the voter data collection system for people with disabilities, increased physical and non-physical accessibility, and strengthened election outreach to be more inclusive so that political participation for people with disabilities can be realized in a meaningful and equal manner.